Pad-Based CDM ESD Protection Methods Are Faulty - Mengfu Di; Cheng Li; Zijin Pan; Albert Wang (IEEE Journal of the Electron Devices Society, 2020)
Charged device model (CDM) electrostatic discharge (ESD) protection remains a huge challenge for integrated circuit (IC) reliability designs. The “internal-oriented” CDM model and the “external-oriented” human body model (HBM) describe fundamentally different ESD phenomena. Through the comprehensive analysis, this article concludes that the classic pad-based ESD protection methods, commonly used for “from-external-to-internal” HBM ESD protection, are theoretically not working for “from-internal-to-external” CDM ESD protection. It states that the actual internal distribution of static charges within a chip is vitally critical to CDM ESD protection. The discovery explains the potential root cause of the randomness and uncertainty of pad-based CDM ESD protection designs commonly observed today, hence calls for new CDM ESD protection solutions.